The witchmaster's key - Dixon, Franklin W. (New York : Grosset & Dunlap, 1976)
The Hardy boys' investigation of a museum robbery in England arouses the anger of a coven of black witches
Keywords: Witches -- Fiction; Detective and mystery stories; English fiction; England -- Fiction